New findings on green sweet pepper (Capsicum annum) pectins: Rhamnogalacturonan and type I and II arabinogalactans - do Nascimento, Georgia Erdmann; Iacomini, Marcello; Cordeiro, Lucimara M.C. (Carbohydrate polymers, 2017)
•Detailed structural characterization of sweet pepper pectic polysaccharides is described.•It presented a high methylesterified (DM=85%) homogalacturonan.•It also had type I and type II arabinogalactans anchored in type I rhamnogalacturonan. Polysaccharides were extracted from sweet pepper (Capsicum annum) with hot water and named ANW (9% yield). Starch was precipitated by freeze-thaw treatment, while pectic polysaccharides (8% yield) remained soluble and consisted of GalA (67.0%), Rha (1.6%), Ara (6.4%), Xyl (0.3%), Gal (6.7%) and Glc (4.4%). A highly methoxylated homogalacturonan (HG, degree of methylesterification of 85% and degree of acetylation of 5%), and type I and type II arabinogalactans (AG-I and AG-II) were observed in NMR analyses. These were fractionated with Fehling’s solution to give HG (5.5% yield) and AG fractions (0.6% yield). AG-I and AG-II were further separated by ultrafiltration. AG-II (0.2% yield) consisted of Ara (17.1%), Gal (36.0%), Rha (5.6%) and GalA (12.0%), had a molecular weight of 5.3×104g/mol and methylation and 1H/13C HSQC-DEPT-NMR analyses showed that it was anchored in type I rhamnogalacturonan. This is the first study that reports the presence of AG-I and AG-II in sweet pepper fruits.